(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
Client satisfaction surveys have served as a valued appraisal tool to measure quality care in various healthcare settings, but there is a paucity of published research of client satisfaction with allied health professionals in the occupational health setting. The aim of this project was therefore to evaluate client satisfaction with allied health professionals in an occupational health setting. A survey was developed by the therapy team for the purpose of this project following a literature search. The survey consisted of four components: (a) demographic section, (b) satisfaction with therapy and therapist, (c) impact on attendance at work and (d) open-ended comments. The survey was piloted with appropriate modifications made prior to use. The demographic data indicated that the therapy team provided services to a diversity of clients. In all domains of satisfaction with therapy and therapist clients reported more than ninety percent satisfaction. This survey revealed that the therapy team has made a significant impact in supporting clients who were at work to remain at work and reduce the likeliness of future sickness absence. For those absent from work the therapy team made a significant impact in supporting clients return to work but has not made a significant impact on reducing the likeliness of future sickness absence. The positive experiences reported by clients were support, caring, therapy impact and quality of care and the areas for improvement reported were streamlining the onward referral process and reducing waiting times. The information provided by clients will be used to improve and refine the therapy services.